(untitled) (Metallurgy and Foundry Engineering, 2017)
This study compares the numerically determined strain distributions after the application of the method of equal-channel angular pressing. The calculations were performed for four variants of the channel cross-sectional shapes – square, circular, and two rectangular ones with the same transverse surface area. The calculation results have been demonstrated as maps of effective strain distribution in the stabilized process.